Pengambilan Keputusan Kepala Desa Kalebarembeng Kecamatan Bontonompo Kabupaten Gowa - Hidayat, Rahmat; Muhammadiah, Muhammadiah; Nasrulhaq, Nasrulhaq (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2021)
The purpose of this study was to determine how the decision-making of Kalebarembeng Village Head, Bontonompo District, Gowa Regency. The number of informants in this study was 11 people. This study used qualitative with a type of phenomenological research that emphasized the subjectivity of human life experiences. Data collection techniques were the method of observation, interviews and documentation. Data analysis used interactive analysis models. The results showed that the decision-making of the Kalebarembeng Village Head of Bontonompo District of Gowa Regency was seen from the aspect of the Village Head's Intuition in the decision-making process which was not good enough because it often prioritized feelings, the aspect of the village head's experience was still lacking because the community with the hamlet head said that the community it should be involved in meetings or deliberations, sometimes it is still not involved. The fact of decision making in the kalebarembeng village government scope concluded that was still not good to be seen from the criticism from the community, but the authority and rational aspects had been going well and made sense. Keywords: Decision Making, Kalebarembeng Village Head